2007
DOI: 10.1016/j.str.2007.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Structural Roles of Monovalent Cations in the HDV Ribozyme

Abstract: The hepatitis delta virus (HDV) ribozyme catalyzes viral RNA self-cleavage through general acid-base chemistry in which an active-site cytidine and at least one metal ion are involved. Monovalent metal ions support slow catalysis and were proposed to substitute for structural, but not catalytic, divalent metal ions in the RNA. To investigate the role of monovalent cations in ribozyme structure and function, we determined the crystal structure of the precursor HDV ribozyme in the presence of thallium ions (Tl(+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(101 citation statements)
references
References 25 publications
4
96
1
Order By: Relevance
“…The inline conformation needed for the reaction seems unaffected by the ionic environment both in our calculations and in the work by Ganguly et al (2014). Although it has been suggested that the overall HDVr fold will not be altered when only monovalent ions are present (Ke et al 2007), the local conformation could be altered upon charge/protonation state changes. As shown recently, the HDVr inline conformation highly correlates with the protonation state of C75 (Sripathi et al 2014).…”
Section: Comparison Of Metal-bound Statessupporting
confidence: 45%
See 1 more Smart Citation
“…The inline conformation needed for the reaction seems unaffected by the ionic environment both in our calculations and in the work by Ganguly et al (2014). Although it has been suggested that the overall HDVr fold will not be altered when only monovalent ions are present (Ke et al 2007), the local conformation could be altered upon charge/protonation state changes. As shown recently, the HDVr inline conformation highly correlates with the protonation state of C75 (Sripathi et al 2014).…”
Section: Comparison Of Metal-bound Statessupporting
confidence: 45%
“…Detailed biochemical and kinetic studies have revealed multiple functional divalent metal binding sites and demonstrated that molar concentrations of monovalent ions alone can support catalysis (Nakano et al 2001(Nakano et al , 2003. Sitebound metal ion interactions have been identified and characterized via crystallography (Ke et al 2004(Ke et al , 2007Chen et al 2010), spectroscopy ), chemical probing experiments (Chen et al , 2013Lévesque et al 2012;Thaplyal et al 2015), and molecular simulation (Lee et al 2011;Veeraraghavan et al 2011a,b;Chen et al 2013). Moreover, pH-rate profiles for the reaction in the absence of Mg 2+ and for mutants designed to disrupt binding of the proposed active site ion are inverted relative to the reaction of the native HDVr in Mg 2+ Chen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Tl þ , a K þ isostere, was observed making an inner sphere contact with both the 2 0 hydroxyl of the À1 nucleotide and the scissile phosphate. 81 The active site contained two other Tl þ ions, which were displaced by a single Co NH 3 ð Þ 6 3þ when it was soaked into the crystals. In the crystal structure of the ribozyme product, the active site appears to accommodate two different weakly bound metal ions at slightly distinct locations.…”
mentioning
confidence: 99%
“…35,36,81 It is clear that the RNA strand has to make a sharp turn at the cleavage site to accommodate the leader, which makes no base-specific contacts with the ribozyme. This observation correlates well with the lack of sequence conservation upstream of the cleavage site among HDV-like ribozymes, although the identity of the À1 nucleotide affects the metal ion preference of the active site, suggesting that the base may affect the precise orientation of the scissile phosphate in the active site.…”
mentioning
confidence: 99%
“…U6 mammalian promoter requires to have a G at the 5′ end of the transcript [28]. Transcriptional expression can be improved by inserting self-processing elements, such as HDV ribozyme and tRNAs, at the 5′ or 3′ end to prevent potential degradation of the transcript [49,83]. Processing elements can also be exploited to multiplex several gRNAs in a row by collocating those element between each gRNAs [17] (Fig.…”
Section: The Grna Characteristics and Extensionsmentioning
confidence: 99%